Application of the Convention on the Prevention and Punishment of the Crime of Genocide (Croatia v. Serbia). (2022) - Unknown
Abstract : 1 Human rights — Genocide — Definition of genocide — Convention for the Prevention and Punishment of the Crime of Genocide, 1948 — Actus reus of genocide — Mens rea — Specific intent to destroy protected group — Dolus specialis — Proof — Whether existence of intent can be inferred from pattern of conduct — Relationship between genocide and other violations of humanitarian law and human rights — Ethnic cleansing — Responsibility for genocide — Whether genocide established in principal claim — Whether genocide established in counter-claim — Armed conflict in territory of Croatia in 1991-95 — Whether breaches of Genocide Convention International Court of Justice — Jurisdiction — Scope — Consent to jurisdiction — Basis for jurisdiction — Article IX of Genocide Convention — Court confined to disputes regarding genocide — Whether dispute between Parties falling within Article IX of Genocide Convention — Respondent raising preliminary objections relating to jurisdiction of Court and admissibility of Application — Whether Court having jurisdiction to entertain Croatia's Application International Court of Justice — Jurisdiction — Scope — Basis for jurisdiction — Article IX of Genocide Convention — Whether Court having jurisdiction — Respondent's first preliminary objection — Capacity to participate in proceedings before Court — Articles 34 and 35 of Statute of Court — Whether Parties satisfying general conditions — Whether Respondent having access to Court on basis of Article 35(1) of Statute — Admission to United Nations on 1 November 2000 — Whether Respondent acquiring status of party to Statute of Court on 1 November 2000 — Whether Court "open" to Respondent — Issues of jurisdiction ratione materiae — Declaration and Note of 27 April 1992 — Nature and effect on position of the Federal Republic of Yugoslavia in relation to Genocide Convention — Whether declaration having effect of notification of succession to treaties — Whether Respondent party to Genocide Convention, including Article IX, at date of institution of proceedings until at least 1 November 2000 — Whether Court having jurisdiction to entertain Croatia's Application International Court of Justice — Jurisdiction — Scope — Basis for jurisdiction — Article IX of Genocide Convention — Whether Court having jurisdiction — Respondent's second preliminary 2 objection — Issues of jurisdiction ratione temporis — Whether claims based on acts and omissions which took place prior to 27 April 1992 beyond jurisdiction of Court and inadmissible — Distinction between objection to jurisdiction and objection to admissibility — Whether second preliminary objection possessing an exclusive preliminary character — Whether possible to determine questions raised by objection without determining issues properly pertaining to merits — Whether Court having jurisdiction to entertain Croatia's Application International Court of Justice — Jurisdiction — Scope — Basis for jurisdiction — Article IX of Genocide Convention — Whether Court having jurisdiction — Respondent's third preliminary objection — Whether claims referring to submission of persons to trial within jurisdiction of Court — Whether claims concerning provision of information on missing Croatian citizens within jurisdiction of Court — Whether claims concerning return of cultural property within jurisdiction of Court — Whether Court having jurisdiction to entertain Croatia's Application International Court of Justice — Jurisdiction — Scope — Basis for jurisdiction — Article IX of Genocide Convention — Issues of jurisdiction and admissibility to be determined at merits stage — Issues of jurisdiction ratione temporis — Whether Court's jurisdiction extending to acts prior to 27 April 1992 — Whether provisions of Genocide Convention retroactive — Logic — Article 28 of Vienna Convention on the Law of Treaties, 1969 — Whether acts said to have occurred before 27 April 1992 falling within scope of jurisdiction under Article IX due to Article 10(2) of International Law Commission's Articles on State Responsibility — Whether acts said to have occurred before 27 April 1992 falling within scope of jurisdiction under Article IX due to law of State succession — Whether Respondent bound by obligations under Genocide Convention — Whether Court having jurisdiction to entertain Croatia's Application with respect to acts prior to 27 April 1992 State succession — Socialist Federal Republic of Yugoslavia — Dissolution — Republics becoming independent States — Distinction between successor State and continuing State — Federal Republic of Yugoslavia claiming to be continuation of the Socialist Federal Republic of Yugoslavia — Serbia and Montenegro — Republic of Serbia — Consent to jurisdiction of International Court 3 of Justice — Whether Serbia sole Respondent — Treaty commitments — Genocide Convention — Whether Federal Republic of Yugoslavia party by succession to Genocide Convention — Membership of United Nations — Status and position of Respondent State in relation to the Statute of the International Court of Justice and to Genocide Convention Treaties — Accession — Parties — Signature — Ratification — Genocide Convention — Process by which State becoming bound by treaty as successor State or remaining bound by treaty as continuing State — Signature of Genocide Convention by the Socialist Federal Republic of Yugoslavia on 11 December 1948 — Socialist Federal Republic of Yugoslavia depositing instruments of ratification, without reservation, on 29 August 1950 — Whether the Federal Republic of Yugoslavia party by succession to Genocide Convention from beginning of its existence as a State — Declaration and Note of 27 April 1992 — Nature and effect on position of the Federal Republic of Yugoslavia in relation to Genocide Convention — Whether Serbia party to Convention at date of Application on 2 July 1999 Treaties — Interpretation — Application — Genocide Convention — Applicable law — Article II of Genocide Convention — Constituent elements of genocide — Actus reus and mens rea of genocide — Dolus specialis — Requirement of specific intent to destroy group in whole or part — Evidence — Mens rea of genocide — Meaning and scope of destruction of group — Destruction of group in part — Evidence of dolus specialis — Actus reus of genocide — Relationship between Genocide Convention and international humanitarian law — Meaning and scope of physical acts — Whether genocide established in principal claim — Whether alleged acts established — Whether falling into categories listed in Article II of Genocide Convention — Whether committed with intent to destroy protected group, in whole or in part — Quantitative element — Geographic location — Pattern of conduct — Whether genocide established in counter-claim — Whether breaches of Genocide Convention International criminal law — Genocide — Definition of genocide — Obligations under Genocide Convention — Role of International Criminal Tribunal for the former Yugoslavia — Proof of genocide 4 Evidence before international courts and tribunals — Evidence — Burden of proof — Standard of proof — Methods of proof — Relevance of findings by International Criminal Tribunal for the Former Yugoslavia — Whether conclusive evidence crimes committed — Whether conclusive evidence regarding attribution of acts State responsibility — Attribution — Responsibility of State for acts of State organs — Engagement of international responsibility of acts unlawful even if author of acts acting contrary to instructions or exceeding authority — International Law Commission's Articles on State Responsibility 2001 — Relevance — Determination of responsibility of State if genocide established — Whether genocide established — Whether breaches of Genocide Convention War and armed conflict — Armed conflict in territory of Croatia as it had existed within the Socialist Federal Republic of Yugoslavia in 1991-95 — Allegations of acts of genocide — Whether breaches of Genocide Convention